Non-Monetary Indicators and Multiple Dimensions: The ESRI Approach to Poverty Measurement - Watson, Dorothy; Whelan, Christopher T.; Maître, Bertrand; Williams, James (The Economic and Social Review, 2017)
This paper seeks to distil the lessons on poverty measurement from a period that extends back to the early days of poverty research at the ESRI in the mid to late 1980s. What was the problem to which non-monetary indicators was the solution? How were the indicators chosen and justified? What have we learned about the role and limitations of non-monetary indicators? What are the key future challenges? It makes clear that a variety of approaches are required to do justice to the complex and multi-faceted nature of poverty. The essential elements of the definition of poverty underpinning the research at the ESRI has been that poverty is something rooted in a lack of resources that results in exclusion from the customary standard of living. In pursuing such understanding over the last thirty years, the ESRI research programme has sought to develop measures exhibiting satisfactory levels of reliability and validity which are subject to re-evaluation in changing circumstances. The paper demonstrates that, viewed from a broader sociological perspective on social stratification, the fact that the complexities of poverty and social exclusion are far from being adequately captured by a single indicator relating to current disposable income is not surprising. Measurement of poverty must be viewed within a broader framework relating to the socially structured nature of disadvantage and social inequality. As a consequence poverty targets need to be framed in a manner which focuses attention on long-term structural issues.